2001
DOI: 10.1016/s0378-4371(01)00460-5
|View full text |Cite
|
Sign up to set email alerts
|

When human walking becomes random walking: fractal analysis and modeling of gait rhythm fluctuations

Abstract: We present a random walk, fractal analysis of the stride-to-stride uctuations in the human gait rhythm. The gait of healthy young adults is scale-free with long-range correlations extending over hundreds of strides. This fractal scaling changes characteristically with maturation in children and older adults and becomes almost completely uncorrelated with certain neurologic diseases. Stochastic modeling of the gait rhythm dynamics, based on transitions between di erent "neural centers", reproduces distinctive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
158
2
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(174 citation statements)
references
References 21 publications
8
158
2
6
Order By: Relevance
“…We first studied the stride-to-stride fluctuations present in healthy adults in order to gain insight into normal locomotor function and its control mechanisms and thereby better appreciate pathological deviations (Hausdorff, Ashkenazy et al, 2001;Hausdorff et al, 1996). Variability, the magnitude of the stride-to-stride fluctuations, and stride dynamics, how the stride fluctuates with time, independent of the magnitude, may rely upon different control mechanisms.…”
Section: First Evidence Of Fractal-like Fluctuations In Gaitmentioning
confidence: 99%
See 1 more Smart Citation
“…We first studied the stride-to-stride fluctuations present in healthy adults in order to gain insight into normal locomotor function and its control mechanisms and thereby better appreciate pathological deviations (Hausdorff, Ashkenazy et al, 2001;Hausdorff et al, 1996). Variability, the magnitude of the stride-to-stride fluctuations, and stride dynamics, how the stride fluctuates with time, independent of the magnitude, may rely upon different control mechanisms.…”
Section: First Evidence Of Fractal-like Fluctuations In Gaitmentioning
confidence: 99%
“…These include deterministic models, stochastic models, as well as combinations of the two (Ashkenazy et al, 2002;Hausdorff, Ashkenazy et al, 2001;Hausdorff, Peng et al, 1995;Kurz & Stergiou, 2005;West & Latka, 2005;West & Scafetta, 2003). Some of these models are able to reproduce and explain the fractal-like fluctuations and many of the observed alterations with aging and disease have been captured as well.…”
Section: Modeling the Stride-to-stride Fractal Fluctuationsmentioning
confidence: 99%
“…By using pressure sensors in the shoe (HausdorV et al 1995), it could be demonstrated that gait inter-cycle variability is signiWcantly higher in faller than non-fallers and young subjects (HausdorV et al 1997). Moreover, using the same sensors, it could be demonstrated that the long-range variability in gait patterns is strongly related to degree of functional impairment (HausdorV et al 2001). …”
Section: Assessment Of Balance and Gaitmentioning
confidence: 99%
“…This suggests an adaptive process aimed at allowing greater stabilization around the joint (Peterson and Martin, 2010;Schmitz et al, 2009). This seems to be supported by the fact that aging can lead to loss of balance (Woollacott, 1993) and stability in gait (Hausdorff, 2007;Hausdorff et al, 2001). Therefore, the larger amount of co-activation displayed by the elderly for a given velocity might contribute to further increase the stability.…”
Section: Introductionmentioning
confidence: 96%